2016
DOI: 10.3928/01477447-20160526-07
|View full text |Cite
|
Sign up to set email alerts
|

Taper Failure After Large-Diameter Metal-on-Metal Total Hip Arthroplasty

Abstract: The use of metal-on-metal bearing surfaces for total hip arthroplasty increased dramatically in the past decade for a variety of reasons, including the advantage of using larger-diameter femoral heads to reduce instability. However, recent research suggesting negative outcomes and high failure rates associated with some of these implants has decreased their use. Further, the use of larger-diameter femoral heads on relatively small femoral neck tapers has caused concern about localized corrosion at this junctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…The design and manufacturing parameters of the modular interface can also affect the fretting motion. A large diameter of the metal-on-metal bearing surface often results in more serious fretting corrosion [52]. The effects of taper shape on fretting corrosion were studied by Tan et al [53].…”
Section: Modular Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…The design and manufacturing parameters of the modular interface can also affect the fretting motion. A large diameter of the metal-on-metal bearing surface often results in more serious fretting corrosion [52]. The effects of taper shape on fretting corrosion were studied by Tan et al [53].…”
Section: Modular Interfacementioning
confidence: 99%
“…Besides, the bearing surface between the femoral head and the acetabular cup can also affect the fretting corrosion at the modular interface, and the friction torque at the bearing surface plays an important role in this process. Under adverse conditions, metal-on-metal bearing surfaces with large diameters can produce a high coefficient of friction, leading to severe fretting corrosion [3,52]. The weight of the patient can directly affect the fretting corrosion damage at the cone neck assembly [56].…”
Section: Modular Interfacementioning
confidence: 99%
“…The common denominator for these studies is that adverse reactions are found more often than anticipated, and clinical manifestations vary [13][14][15]. The awareness of implant reactions might partially explain the rise, but there is substantial evidence [16][17][18][19][20] that this is a real clinical phenomenon, although some of these reactions can be asymptomatic.…”
Section: Introductionmentioning
confidence: 99%